Evento de seca extrema promove o aninhamento e reduz a diversidade beta temporal da comunidade de invertebrados bentônicos em lagos rasos. - Silva, Jaqueline Dantas da (2022)
Extreme hydrological events, such as droughts, are becoming increasingly frequent and lasting, altering the structure and functioning of aquatic ecosystems. Extreme drought may be able to eliminate species that are not able to persist in this condition. In this context, it was investigated whether prolonged extreme droughts can cause the nestedness pattern and affect the temporal beta diversity of the benthic invertebrate community in areas that commonly undergo flooding processes, such as the lagoons of the upper Paraná River floodplain. For this, samples of benthic invertebrates were used in shallow lakes of the floodplain, in a period in which there was a record of a prolonged extreme drought. A high degree of nestedness of the benthic invertebrate community was observed in most of the sampled environments. It was also found that the lower the depth of the pond, the greater the degree of nestedness of the community. And that this degree of nestedness increases with the duration of prolonged extreme drought. Concomitantly, it was found that the temporal beta diversity reduced over the sampled period, that is, the species composition became increasingly similar as the extreme drought progresses. During the entire period of prolonged extreme drought, the predominant component for the change in composition in the environments was the loss of species. Although there was a change in the composition of the community, it was not significantly affected by the reduction in the depth of the environments, only by the duration of the prolonged extreme drought. In general, extreme drought events can cause negative impacts on the community, resulting in the selective extinction of species and the homogenization of the benthic invertebrate community. As these extreme events are predicted to increase in duration and frequency in the coming years, the impacts on these invertebrates could be even more intense and result in a major loss of biodiversity in these aquatic ecosystems.